2011
DOI: 10.1002/ange.201104285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Pressure on MOF‐5: Guest‐Induced Modification of Pore Size and Content at High Pressure

Abstract: Unter Druck: Die erste kristallographische Untersuchung des Metall‐organischen Gerüsts MOF‐5 unter hohem Druck ergab als erste Folge der Druckzunahme, dass das druckübertragende Fluid in die Poren gepresst wird. Bei weiterer Druckerhöhung nahm der Poreninhalt erheblich ab, weil Lösungsmittel aus den Poren austrat, und bei Drücken oberhalb von 3.2 GPa ging schließlich die Kristallinität vollständig verloren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Single crystals of MOF-520 were loaded in a DAC with 4:1 methanol:ethanol as the pressure transmitting medium (PTM), and diffraction data were collected on beamline 12.2.2, from ambient pressure up to 2.82 GPa, at which pressure the crystal became amorphous. This amorphization is not unusual, in that the high pressure pushes the PTM into the pores, which degrades the long-range order of the crystal [72]. This invasion of PTM was quantified by examining the unit cell dimensions for an increase in volume, as well as determining the unassigned electron count using the program SQUEEZE [73].…”
Section: Chemistrymentioning
confidence: 99%
“…Single crystals of MOF-520 were loaded in a DAC with 4:1 methanol:ethanol as the pressure transmitting medium (PTM), and diffraction data were collected on beamline 12.2.2, from ambient pressure up to 2.82 GPa, at which pressure the crystal became amorphous. This amorphization is not unusual, in that the high pressure pushes the PTM into the pores, which degrades the long-range order of the crystal [72]. This invasion of PTM was quantified by examining the unit cell dimensions for an increase in volume, as well as determining the unassigned electron count using the program SQUEEZE [73].…”
Section: Chemistrymentioning
confidence: 99%
“…Previous studies of these materials under pressure had shown that the pressure transmitting medium could enter the pores of the framework (figure 5a), affecting its behaviour at high pressures [39]. Graham et al [37] have recently studied the prototypical MOF, MOF-5 [Zn 4 O(BDC) 3 , BDC = 1,4-benzenedicarboxylate] to 3.2 GPa on beamline I19 at DLS. In their study, the authors used diethyl formamide (DEF) as the pressure transmitting medium as more volatile media, such as alcohols, caused the single crystal to become polycrystalline (figure 5b).…”
Section: Example 3: High-pressure Single-crystal Studies Of Metal-orgmentioning
confidence: 99%
“…Beamline I19 has played a pivotal role in the recent development and exploitation of highpressure crystallographic methods and it has already contributed to landmark high-pressure investigations of well-known MOFs [30][31][32][33][34][35]. We have begun studies of the behaviour of our own more flexible MOFs, several of which possess outstanding gas storage or separation properties, at pressures of up to 100 kbar.…”
Section: Continuing and Future Activitiesmentioning
confidence: 99%